Sparse scalp hair and vision loss: think hypotrichosis with juvenile macular dystrophy. Issue 10 (23rd October 2019) - Narayan, Akshay; Moosajee, Mariya
Abstract : Here, we report the diagnostic challenge of a female patient of Russian descent with autosomal recessive hypotrichosis with juvenile macular dystrophy (HJMD). She presented to dermatology age one and a half years with sparse hair growth on her scalp, her parents were reassured this would grow, but it never manifested. She was found to be hypermetropic and prescribed glasses from age 2 but no retinal findings were noted. At age 23 years, the patient undertook an internet search and discovered the association of symptoms pointing towards HJMD. She sought genetic testing, revealing a homozygous missense mutation in Cadherin-3 ( CDH3 ) gene. The patient presented to our Genetic Eye Disease Service at Moorfields Eye Hospital age 27 years, with reduced colour, central distance and near vision. Fundus examination and imaging confirmed atrophic macular changes. Currently, HJMD has no treatment, she wears a wig, UV-protected sunglasses in sunlight and maintains a healthy balanced diet.